Efficacy of Dexmedetomidine versus Ketofol for Sedation of Postoperative Mechanically Ventilated Patients with Obstructive Sleep Apnea - Hatem Elmoutaz Mahmoud; Doaa Abou Elkassim Rashwan (Critical Care Research and Practice)
Patients with sleep apnea are prone to postoperative respiratory complications, requiring restriction of sedatives during perioperative care. We performed a prospective randomized study on 24 patients with obstructive sleep apnea (OSA) who underwent elective surgery under general anesthesia. The patients were equally divided into two groups: Group Dex: received dexmedetomidine loading dose 1 mcg/kg IV over 10 min followed by infusion of 0.2–0.7 mcg/kg/hr; Group KFL: received ketofol as an initial bolus dose 500 mcg/kg IV (ketamine/propofol 1 : 1) and maintenance dose of 5–10 mcg/kg/min. Sedation level (Ramsay sedation score), bispectral index (BIS), duration of mechanical ventilation, surgical intensive care unit (SICU) stay, and mean time to extubation were evaluated. Complications (hypotension, hypertension, bradycardia, postextubation apnea, respiratory depression, and desaturation) and number of patients requiring reintubation were recorded. There was a statistically significant difference between the two groups in BIS at the third hour only (Group DEX 63.00 ± 3.542 and Group KFL 66.42 ± 4.010, p value = 0.036). Duration of mechanical ventilation, SICU stay, and extubation time showed no statistically significant differences. No complications were recorded in both groups. Thus, dexmedetomidine was associated with lesser duration of mechanical ventilation and time to extubation than ketofol, but these differences were not statistically significant.